1994
DOI: 10.1126/science.7973635
|View full text |Cite
|
Sign up to set email alerts
|

p53 Status and the Efficacy of Cancer Therapy in Vivo

Abstract: The therapeutic responsiveness of genetically defined tumors expressing or devoid of the p53 tumor suppressor gene was compared in immunocompromised mice. Tumors expressing the p53 gene contained a high proportion of apoptotic cells and typically regressed after treatment with gamma radiation or adriamycin. In contrast, p53-deficient tumors treated with the same regimens continued to enlarge and contained few apoptotic cells. Acquired mutations in p53 were associated with both treatment resistance and relapse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
780
4
19

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,386 publications
(817 citation statements)
references
References 18 publications
14
780
4
19
Order By: Relevance
“…In point of fact, a number of studies raise the possibility that cells lacking p53 activity might more readily survive certain forms of cancer therapy (Lowe et al, 1994).…”
Section: Amino-terminal Region Of P53mentioning
confidence: 99%
“…In point of fact, a number of studies raise the possibility that cells lacking p53 activity might more readily survive certain forms of cancer therapy (Lowe et al, 1994).…”
Section: Amino-terminal Region Of P53mentioning
confidence: 99%
“…Recently, evidence has been obtained that wild-type as well as most mutant p53 proteins can down-regulate Bcl-2 expression in vitro and in vivo (Haldar et al, 1994;Selvakumaran et al, 1994;. Mutations in the p53 tumour-suppressor gene are a marker of poor prognosis in node-negative breast cancer (Isola et al, 1992) and experimental data have demonstrated increased resistance to doxorubicin and gamma irradiation in tumours lacking functional p53 (Lowe et al, 1994). We also evaluated the predictive value of Bcl-2 expression on responsiveness in the subgroup of patients with p53-negative tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical and experimental trials have shown the inactivation of p53 to be correlated with resistance to chemotherapy in colorectal cancers (Lowe et al, 1994;Bunz et al, 1999). p53 is a transcriptional factor, which induces its target genes, such as p21, Bax, Noxa, and Puma, to regulate either cell cycle arrest or apoptosis in response to chemotherapeutic drugs (el-Deiry et al, 1993;Miyashita and Reed, 1995;Vogelstein et al, 2000;Oda et al, 2000;Yu et al, 2003).…”
mentioning
confidence: 99%